Socially significant diseases in the disability nosological structure in the elderly in the Russian Federation - S. B. Shevchenko; S. N. Puzin; M. A. Shurgaya; M. A. Osadchuk (Сеченовский вестник, 2016)
Disability is an essential criterion for public health, which identiﬁes high mortality rates, low longevity and quality of life. The article analyzes the problem re disability in the adult population in the Russian Federation with focus on the major category of elderly persons. The results of the study in the proportion of older people with disabilities in the disability re-structure, dynamics and level of the repeated disability due to all classes of diseases according to ICD 10 for a long period (2005–2014). The results of the analysis indicate about the dynamics of increase of re-entry for senior citizens on disability due to basic socially signiﬁcant diseases in the Russian Federation by reducing this rate among young and middle-age. Determined the leading nosologies in the structure of the secondary disablement: diseases of the circulatory system (1 rank), malignant neoplasms (rank 2), illnesses of bone-muscular system (rank 3), diseases of the organ of vision (4 rank), diseases of the endocrine and nervous systems (5th – 6th ranking place), mental disorders (7 rank), the eﬀects of trauma and poisoning (8 rank). Especially the growing dynamics of the level of disability seen in the categories of older people with disabilities due to malignant neoplasms, over a ten-year period increased from 10.1 to 41.6 per 10 thousand of the relevant population.